Comparison of Zidovudine and Tenofovir Based Regimens With Regard to Health-Related Quality of Life and Prevalence of Symptoms in HIV Patients in a Kenyan Referral Hospital - Etenyi, Jilian O.; Okalebo, Faith A.; Oluka, Margaret; Sinei, Kipruto A.; Osanjo, George O.; Kurdi, Amanj; Meyer, Johanna C.; Godman, Brian; Opanga, Sylvia (Frontiers in Pharmacology, 2018)
Introduction: Zidovudine and tenofovir form the backbone of antiretroviral therapy in Kenya. However, their side-effects may affect the quality of life of patients. Objective: To compare the Health Related Quality of Life (HRQoL) of adult patients on tenofovir versus zidovudine based regimens in a referral hospital in Kenya to provide future guidance. Methods: A comparative cross sectional study amongst adult out-patients on either tenofovir or zidovudine was undertaken in Kenyatta National Hospital between 2015 and 2016. The Medical Outcome Study HIV Health Survey (MOS-HIV) was administered along with other key aspects of treatment. Linear regression analysis was performed to identify determinants of HRQoL. Results: Patients on zidovudine had a higher Physical Health Summary Score (PHSS) and Mental Health Summary Score (MHSS) compared to those on tenofovir. The presence of any symptom of the disease and a stated inability to cope were negatively associated with PHSS, while having a regular source of income improved PHSS. Being on tenofovir, symptom of illness (β=-1.24; 95% CI [-2.253, -0.226]), absence of pain (β=0.413; 95% CI [0.152, 0.674]) and patient stated inability to cope with HIV (β=-1.029; 95% CI [-1.441, -0.617]) affected the MHSS. Patients on tenofovir and second line regimens had more signs and symptoms of illness. Conclusion: Participants on zidovudine based regimens showed a better performance across all aspects of HRQoL. These are considerations for the future